2019
DOI: 10.12968/jowc.2019.28.9.576
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of people with pressure ulcers using one year's routinely collected data in a defined diverse community

Abstract: Objective: To determine if meaningful patient characteristics pertaining to pressure ulcers (PU) can be derived from routinely collected community health data. Methods: A retrospective cohort analysis of records was carried out. To provide a detailed dataset on PU for the community of interest, demographic, general medical and PU data were extracted from mandatory incident reports and audit of electronic and paper medical records. This study is reported in accordance with the RECORD Guidelines from the Equator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Prevalence of PIs varied across settings, from 4-13.7% 124,125 in hospitals, 3.6% in a regional hospital 126 , 5.2% in adults transferred by ambulance 127 , and 8.9% in community services 128 . One study reported 137 PIs in 103 people in a district nursing service 129 , another examined location of heel PIs 130 , and one examined the costs of auditing PI prevalence 131 .…”
Section: Australian Studiesmentioning
confidence: 99%
“…Prevalence of PIs varied across settings, from 4-13.7% 124,125 in hospitals, 3.6% in a regional hospital 126 , 5.2% in adults transferred by ambulance 127 , and 8.9% in community services 128 . One study reported 137 PIs in 103 people in a district nursing service 129 , another examined location of heel PIs 130 , and one examined the costs of auditing PI prevalence 131 .…”
Section: Australian Studiesmentioning
confidence: 99%